MENINGKATKAN KETERAMPILAN MEMBACA PUISI DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL PADA SISWA KELAS X.8 SMAN 2 GOWA KABUPATEN GOWA - Wilda Wijayanti; Nurmia Muin; Nurfathana Mazhud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Poetry Reading Skills is an activity that is still little done in schools. Low students' listening skills will have an impact on their learning achievement. This research aims to improve learning outcomes for reading poetry, the application of audiovisual media can improve the expected poetry reading skills of class X.8 students at SMAN 2 Gowa. This type of research is Classroom Action Research (PTK). Classroom action research aims to improve the quality or solve problems of the subjects studied and observe the level of success or consequences of the actions, to then take additional actions which are perfecting actions or adjustments to conditions and situations in order to achieve good results. In the pre-cycle the average student score was 65 and achieved a KKMP score of 16% or as many as 5 students. In cycle 1 the average student score was 74 and those who achieved KKMP were 58% or 18 students. In cycle II the average student score was 82 and those who achieved KKMP were 100% or as many as 31 students. Based on the results of the research and discussion above, it can be concluded that the application of audiovisual media for learning poetry reading skills in each cycle shows an increase in learning activities which can improve learning outcomes for poetry reading skills in class X.8 students at SMAN 2 Gowa.